Studying on design of a complet pilot plant for processing sandstone ores in Pa Lua – Pa Rong area - Le , Quang Thai; Tran , Van Son; Vu , Khac Tuan; Tran , The Dinh; Trinh , Nguyen Quynh; Doan , Thi Mo; Nguyen , Hong Ha; Bui, Thi Bay; Pham , Minh Tuan; Than , Van Lien (Nuclear Science and Technology, 2015)
Design, construction and operation of a pilot for processing uranium containing ores are important stages in the process of project development of uranium production from ores because uranium contained minerals and the composition of minerals are unstable factors. In this case, pilot needs to be a simulation of a plant in the future, but with upgrade equipment compared that at laboratory scale. Results of lab research were used to select the most appropriate process for ore processing and selection of equipment for each stages. In the circumstance when there has been a lack of experience in processing uranium ores in Vietnam, the design and construction of such a pilot with completed technological procedures are essential. The main purpose of this work is to verify results of lab researches and optimize operational parameters of the process. In addition, several purposes were also considered such as study on the effects of solution circulation/recycling and accummulation of impurities in a long run; obtain necessary and sufficient information for design, cost estimate for investment and operation... The pilot only can achieve the expected objectives when ore sources (including reserves and characteristics) are determined; a complete technological process for obtaining technical uranium (yellowcake) is designed; investment and operational capitals are estimated and these estimates show the costs and benefits of the process. In this article, the authors will focus on the presentation of research results, including data on ore, process technology, material balance, pilot scale, the basic parameters of equipments, installation diagram of equipments, construction, power and water needs identification, preliminary calculation of investment and operational costs.